2023
DOI: 10.3390/bioengineering10020170
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of the Mandibular Lingula and Antilingula by Cone-Beam Computed Tomography

Abstract: The patterns of the lingula and antilingula are crucial surgical reference points for ramus osteotomy. Cone-beam computed tomography (CBCT) provides three-dimensional images, and patient radiation dose is significantly lower for CBCT than for medical CT. The morphology of the mandibular lingula and antilingula of ninety patients (180 sides) were investigated using CBCT. The lingula were classified as having triangular, truncated, nodular, and assimilated shapes. The antilingula were classified as having hill, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…CBCT investigations have proven helpful in studying the ML, offering improved visualization and precise anatomical assessments. [12][13][14]17,[22][23][24] Nevertheless, the results remain controversial, particularly concerning the correlation between genders, angle Even though some studies reported no significant differences between male and female patients, 14,22 our results were consistent with other studies, which have detected such differences and indicated relatively more minor mandibles and, consequently, smaller measurements of the mandibular lingula (ML) in women. The controversy among studies stems from several factors, including participant age, race variations and the reference planes employed for measurements.…”
Section: Ta B L E 3 (Continued)supporting
confidence: 87%
See 4 more Smart Citations
“…CBCT investigations have proven helpful in studying the ML, offering improved visualization and precise anatomical assessments. [12][13][14]17,[22][23][24] Nevertheless, the results remain controversial, particularly concerning the correlation between genders, angle Even though some studies reported no significant differences between male and female patients, 14,22 our results were consistent with other studies, which have detected such differences and indicated relatively more minor mandibles and, consequently, smaller measurements of the mandibular lingula (ML) in women. The controversy among studies stems from several factors, including participant age, race variations and the reference planes employed for measurements.…”
Section: Ta B L E 3 (Continued)supporting
confidence: 87%
“…A sample size of 25 samples per group was determined using G*Power software version 3.1.9.6 (Franz Faul, Kiel University, Germany) based on previous studies, [11][12][13][14] considering their average effect size of 0.37. The significance level (alpha) was set at 5% with β at 0.02 (power of 0.98) to achieve the desired effect size of 0.37 using one-way ANOVA power analysis.…”
Section: Study Groups and Sample Size Calculationsmentioning
confidence: 99%
See 3 more Smart Citations